COMPARISON STUDY OF STUDENT’S MISCONCEPTION LEVEL IN BIOLOGY LEARNING THROUGH CONCTRUCTIVISM TIPE NOVICK AND CONSTRUKTIVIS-COLLABOTRATIV LEARNING METHOD - Meti Indrowati, Yunita Rahmawati, Baskoro Adi P (P Biologi FKIP UNS Surakarta, 2015)
This research aims to know about the differences of missconception level on excretory system material of Student?s grade XIth Science?s graders Senior High School of 4 Surakarta in the school year of 2012/2013 using conctructivism type Novick and constructivis-collabotrativ learning method.This research belonged to a quasi-experiment with quantitative approach. The research was designed using pre-test post-test non-equivalent control group design by applying constructism Type Novick learning method for experiment class 1 and using constructism-collaboratif for experiment class 2. The population of research was all XIth Science?s students of Senior High School of 4 Surakarta in the school year of 2012/2013. The sample of research was the XIth Science?s 5 grade as experiment group 1 and XIth Science?s 6 grade as experiment group 2. The sampling technique used was purposive sampling. Technique of collecting data used was objective test with CRI (Certanty of Response Index) and observation test. The hypothesis testing was conducted using Anacova-test. The data analyzed by SPSS version 16 program help at 5% significance.The hypothesis of research there is the differences student?s misconception level of Student?s grade XIth Science?s graders Senior High School of 4 Surakarta in the school year of 2012/2013 using conctructivism type Novick and constructivis-collabotrativ learning method.The hypothesis result test of student?s misconception level using constructivisme type Novick and constructivis-collaboratif method results as p-value<0,05 (0.002< 0.05), so it can be concluded that there is differences of student?s misconception levels of Student?s grade XIth Science?s graders Senior High School of 4 Surakarta in the school year of 2012/2013. Keywords : Constructivism Type Novick, Constructivis Collaborative, Misconception Level